2016
DOI: 10.1038/srep25221
|View full text |Cite
|
Sign up to set email alerts
|

Fluorographene based Ultrasensitive Ammonia Sensor

Abstract: Single molecule detection using graphene can be brought by tuning the interactions via specific dopants. Electrostatic interaction between the most electronegative element fluorine (F) and hydrogen (H) is one of the strong interactions in hydrogen bonding, and here we report the selective binding of ammonia/ammonium with F in fluorographene (FG) resulting to a change in the impedance of the system. Very low limit of detection value of ~0.44 pM with linearity over wide range of concentrations (1 pM–0.1 μM) is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 34 publications
0
48
0
Order By: Relevance
“…[112] Moreover, the reduced carrier mobility of highly hydrogenated graphene is still sufficient for sensor applications. [113] Fluorographene, on the other hand, was applied for the detection of ammonia, [114] ascorbic acid, and uric acid. [115] The fluorine-enriched material could also be further functionalized with thiol groups for genosensing.…”
Section: Covalent Functionalizationsmentioning
confidence: 99%
“…[112] Moreover, the reduced carrier mobility of highly hydrogenated graphene is still sufficient for sensor applications. [113] Fluorographene, on the other hand, was applied for the detection of ammonia, [114] ascorbic acid, and uric acid. [115] The fluorine-enriched material could also be further functionalized with thiol groups for genosensing.…”
Section: Covalent Functionalizationsmentioning
confidence: 99%
“…7,42 The main advantage of FG for sensing is its high electrocatalytic activity and hence augmented electron transfer, and its specificity toward certain analyte due to the presence of C-F bonds. It is also reported that the highly electronegative fluorine bound to the graphene scaffold would affect the surface properties and sensing performance for various analytes and biomarkers.…”
Section: Fluorographene As a Sensing Platformmentioning
confidence: 99%
“…24 Ammonia is another analyte studied for FG based sensing. 7 Various sensing methods are existing for ammonia due to its importance in diverse industrial and biological processes, and also due to its natural and industrial origin. Low dosages of ammonia can cause problems to human respiratory, skin, eyes etc., and its prolonged exposure can lead to pulmonary oedema, a situation of fluid accumulation in the tissues and air spaces of the lungs.…”
Section: Fluorographene As a Sensing Platformmentioning
confidence: 99%
See 2 more Smart Citations